Analysis of the Contribution of the e-SAMSAT System to Motor Vehicle Tax Revenue at UPTD SAMSAT Tomohon - Tjung, Brilian Pijar Wijaya; Pangerapan, Sonny; Tangkuman, Steven J. (PT FORMOSA CENDEKIA GLOBAL, 2024)
Taxes, as the largest source of state revenue, play an important role in the Indonesian economy. Motor vehicle tax is a levy that must be collected by a company or government agency. The purpose of this study is to evaluate the use of e-SAMSAT in increasing state revenue from motor vehicle taxes, making it easier for people to pay motor vehicle taxes, and knowing whether the eSAMSAT application has met the objectives set by the government. This research uses descriptive qualitative data analysis method. Based on the research findings, e-SAMSAT is a payment method that always increases every year, it's just that it hasn't been able to reach the target for each year. However, the implementation of the e-SAMSAT system has been carried out in accordance with applicable regulations.